Improved Measurement Accuracy Based on Moving Sine-Wave Fitting for Ultrasonic Ranging. (5th April 2022) - Wang, Xuanze; Wang, Aihui; Yin, Jinping; Zhao, Hang; Dong, Zhengqiong; Fan, Yiyan; Zhai, Zhongsheng
Abstract : In ultrasonic ranging system, the time-of-flight (TOF), which acquired by the determination of two special points of ultrasonic echo, is important for accuracy and speed. The published calculation of TOF processing methods is too enormous to affect the real-time performance. To improve its measurement accuracy and speed, we proposed a new algorithm called "moving sine-wave fitting" to calculate the envelope of ultrasonic echo for each calibration point. Then, the absolute feature point (AFP) corresponding to half of the envelope peak can be defined and used to find out the relative feature point (RFP); the linear relationship between the RFPs and the known distances should be obtained referring to calibration points. At last, the distance on the measure can be acquired by using linear interpolation according to the above relationship. The measurement experiments have been performed on a set of distances, which shows a good measurement resolution that the overall measurement accuracy is 0.513 mm, and the linear correlation coefficient between the RFPs and the obtained distances is R 2 = 0.806.